Burnout for Social Sustainability Indicator in Higher Education: A Review and Case-Study - Halim, Lenny; Destyanto, Twin Yoshua Raharjo (Universitas Kristen Maranatha, 2025)
Social sustainability, one of the three pillars of sustainability alongside economic and environmental aspects, has received relatively limited attention, particularly in higher education systems. The wide range of social sustainability indicators makes assessment complex, especially when focusing on educators as internal stakeholders. This study aims to propose a representative measure of social sustainability for lecturers in higher education institutions. Given the multidimensional nature of academic work, a concise indicator is needed to reflect lecturers’ well-being effectively. A PRISMA-based literature review was conducted to identify relevant social sustainability indicators for employees. The review resulted in four main criteria comprising 18 indicators related to employee well-being. The findings were synthesized through an industrial psychology lens by combining literature-based conceptual grouping, indicator prevalence analysis, and the development of a theory-informed conceptual framework, leading to the selection of burnout as a practical indicator of social sustainability in higher education. To demonstrate its application, a case study was conducted involving 41 lecturers from the Faculty of Industrial Technology at Universitas Atma Jaya Yogyakarta. Burnout levels were measured using the BAT-12 scale version 2.0. The results showed that 24.4% of lecturers experienced low (sustainable) burnout levels, while the majority (51.2%) experienced moderate burnout. These findings underscore the need for targeted interventions to mitigate burnout and promote long-term social sustainability.